Alemtuzumab (Campath-1H) in allogeneic stem cell transplantation: where do we go from here? - Chakrabarti, S; Hale, G; Waldmann, H (2004)
Alemtuzumab (Campath-1H) has been widely used for T-cell depletion following both conventional and reduced-intensity conditioning allografts. We studied the impact of alemtuzumab used in vivo and in vitro on infections, immune reconstitution, and allograft outcome. The use of alemtuzumab in vivo following reduced-intensity conditioning and unrelated donor conventional transplantation was associated with durable engraftment and significant reduction in graft-versus-host disease (GVHD) but at the cost of impaired immune reconstitution and increased infectious complications. Alemtuzumab exposure in vitro was associated with durable engraftment and reduced GVHD following conventional transplants without affecting immune recovery to the same extent. Improved results were obtained following a further reduction in the alemtuzumab dose in vitro from 20 mg to 10 mg. Subsequent pharmacokinetic studies on alemtuzumab demonstrated that the antibody persisted at a higher concentration at the time of transplant and for at least 2 months thereafter when used in vivo compared to persistence for less than 30 days when used at 20 mg in vitro. In this context; an antibody with a shorter half-life, like the original rat CD52 antibody Campath-1G, would be preferable. Otherwise, our cumulative experience with alemtuzumab suggests that better results might be achieved by tailoring the dose and mode of antibody use to match the clinical situation. Further studies are needed to optimize the dose of alemtuzumab in vivo and in vitro, determined by the type of conditioning and the graft.